A photo-responsive p-Si/TiO2/Ag heterostructure with charge transfer for recyclable surface-enhanced Raman scattering substrates. Issue 5 (18th January 2022) - Wang, Zhezhe; Lai, Yueting; Cai, Jieyi; Jia, Siyi; Lin, Lin; Feng, Zhuohong; Zheng, Zhiqiang; Xie, Rongrong; Li, Jiabing
Abstract : A Si/TiO2 /Ag heterostructure is prepared as a recyclable SERS substrate with EF of 1.23 × 10 12 and excellent repeatability, which can boost performance effectively by the synergistic contribution of the EM and CT enhancement effects. Abstract : Semiconductor–metal heterostructures are attractive surface-enhanced Raman scattering (SERS)-active materials, which can boost the performance effectively because of the synergistic contribution of the electromagnetic (EM) and charge transfer (CT) enhancement effects. In this paper, a photo-responsive Si/TiO2 /Ag heterostructure is prepared and its SERS is explored. The interfacial energy level alignment promotes its CT, resulting in charge separation and favors the measurement of adsorbed molecules on the Ag domains, leading to the increase of SERS activity. The enhancement factor (EF) of the Si/TiO2 /Ag heterostructure with rhodamine 6G (R6G) as a probe molecule is estimated to be 1.23 × 10 12, possessing excellent repeatability, and the relative standard deviation (RSD) is about 2.09%. Moreover, it can be used to detect glyphosate (Gly) very easily at concentrations as low as 0.1 ppb, which is far lower than the national maximum pesticide residue limit in food. Notably, the Si/TiO2 /Ag SERS substrate possesses UV cleaning performance and can serve as a promising recyclable SERS-active substrate in practical trace detection applications at very low cost.